Significant population structure in Australian Cryptolestes ferrugineus and interpreting the potential spread of phosphine resistance. (June 2018) - Toon, A.; Daglish, G.J.; Ridley, A.W.; Emery, R.N.; Holloway, J.C.; Walter, G.H.
Abstract: An analysis of the population genetics of Cryptolestes ferrugineus, across all major regions in Australia where grain is grown and stored in bulk, provides an initial step in investigating the movement of these insects and implications for the spread of phosphine resistance. Microsatellite data revealed two levels of genetic structure. Across Australia, two clusters were detected, one in eastern Australia (Queensland, New South Wales, Victoria and Tasmania) and Western Australia (Cluster 1) and one in South Australia (Cluster 2). Intermediate between them, in eastern South Australia, are a couple of populations that are equally admixed for the two clusters. Populations in Western Australia and western SA belong to different clusters suggesting that the extensive and arid Nullarbor Plain restricts the natural dispersal of these beetles. Isolation-by-distance and the detection of clustering among local populations suggests there is considerable gene flow at a local scale in C. ferrugineus, and we infer this is by flight. Limited natural gene flow between eastern and western Australia might, in part, explain why extremely high resistance has not been detected in Western Australia. Highlights: C. ferrugineus, has developed very high resistance to the fumigant phosphine. Population structure of C. ferrugineus across Australia was investigated. Genetic structure is related to geographic distance. Local dispersal is frequent and long distance dispersal is restricted. Understanding dispersal of pest will help manage the spread of resistance genes.